A Shared Platform for Studying Second Language Acquisition. (14th December 2016) - MacWhinney, Brian
Abstract : The study of second language acquisition (SLA) can benefit from the same process of datasharing that has proven effective in areas such as first language acquisition and aphasiology. Researchers can work together to construct a shared platform that combines data from spoken and written corpora, online tutors, and Web‐based experimentation. Many of the methods and tools for building this platform are already available as a result of earlier work on corpus sharing in first language acquisition. By working together on a shared platform in a coordinated manner, researchers will be able to construct a rich new empirical basis for the study of SLA.